Teaching technical subjects in English in a community college: a case study / Nor Suraya Aini Ngah - Ngah, Nor Suraya Aini (2008)
Beginning 2007 the Teaching and Learning of Technical subjects in English (TLTSE) was introduced in stages in a number of Institutes of Higher Education (IHE) including Community Colleges. Since its introduction into IHE, no in-depth study has been conducted to evaluate its effectiveness. Therefore, this study investigated the extent of the implementation of TLTSE in a community college located in a district in Kuala Terengganu. The study also investigated the lecturers' and students' perceptions of the policy as well as the challenges they faced in implementing TLTSE. This study adopted a descriptive correlation design that employed both qualitative and quantitative approaches. The instrumentation involved the use of 2 sets of questionnaires and 2 sets of semi-structured interviews. The data collection involved a sample of 42 technical lecturers and 94 final semester students studying at Kolej Komuniti Kuala Terengganu (KKKT). Semi-structured interviews were conducted with 10 randomly selected lecturers and 10 randomly selected students. The findings of the study revealed that both lecturers and students realised the importance of English in their fields of study as it was the way forward. Nevertheless both parties viewed the policy negatively and this left the implementation of TLTSE much to be desired. The study also indicated that gender, teaching experience and academic qualifications were all significant contributing factors to lecturers' perceptions and attitudes towards the TLTSE policy. Besides that the challenges that the lecturers faced included their limited language proficiency, lack of motivation and recognition from the college authority, time constraints and inappropriate staff development programmes. Lecturers also revealed that the student factors such as their limited proficiency, lack of interest and their low academic achievement were also challenges they faced in making the policy a reality. On the other hand students cited their limited language proficiency, difficulty in comprehending English, interest in the language as well as their limited academic achievement as challenges they faced in the implementation of the policy. All these findings reveal that a number of mechanisms need to be put in place before the full implementation of the policy can be realised.